EVALUATION OF A COMBINATION OF GINGIVAL PHYSIOTHERAPY, FLOSSING, AND BRUSHING TECHNIQUE THROUGH IN-OFFICE OBSERVATION - BHATNAGAR, ANAND; BHATNAGAR, EVA (International Journal of Current Pharmaceutical Research, 2023)
Objective: Oral physiotherapy is described as the maintenance of oral hygiene, and its goal is the daily, full elimination of plaque with the least amount of work, time, and equipment feasible. Methods: Materials and procedures In order to evaluate the brushing time, the effective duration of brushing, the brushing pattern, the order of sextants, and the use of dental floss, 30 patients aged 18 to 65 were divided into two groups, one without prior instruction, and the other in which the technique of modified Stillman brushing and flossing was explained to them. Results: Despite instruction in hygiene techniques, better results of instruction were found in the control group. Conclusion: Brushing technique was clearly preserved in the control group, although 10% had deficiencies. With this method, we can demonstrate the effectiveness of teaching a certain brushing technique only to typodont patients, probably, some additional method would strengthen the oral physiotherapy skills of the patient.